2021
DOI: 10.3390/cancers13051161
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Sequelae in Women with a History of Localized Breast Cancer: Results from the French VICAN Survey

Abstract: Breast cancer (BC) remains complex for women both physically and psychologically. The objectives of this study were to (1) assess the evolution of the main sequelae and treatment two and five years after diagnosis in women with early-stage breast cancer, (2) explore patterns of sequelae associated with given sociodemographic, clinical, and lifestyle factors. The current analysis was based on 654 localized BC patients enrolled in the French nationwide longitudinal survey “vie après cancer” VICAN (January–June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Delrieu et al found an association between decreased physical activity compared with prediagnosis and higher symptom burden, but no association between BMI and symptom burden in 5-year BCSs. 38 The association between higher BMI and high symptom burden is however reported in another study of BCSs 1-5 years after diagnosis. 13 Higher BMI has also been associated with several of the LEs studied separately including pain, fatigue, and arm problems, 36,37,39 as has physical inactivity with fatigue.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Delrieu et al found an association between decreased physical activity compared with prediagnosis and higher symptom burden, but no association between BMI and symptom burden in 5-year BCSs. 38 The association between higher BMI and high symptom burden is however reported in another study of BCSs 1-5 years after diagnosis. 13 Higher BMI has also been associated with several of the LEs studied separately including pain, fatigue, and arm problems, 36,37,39 as has physical inactivity with fatigue.…”
Section: Discussionmentioning
confidence: 88%
“…Delrieu et al. found an association between decreased physical activity compared with prediagnosis and higher symptom burden, but no association between BMI and symptom burden in 5‐year BCSs 38 . The association between higher BMI and high symptom burden is however reported in another study of BCSs 1‐5 years after diagnosis 13 .…”
Section: Discussionmentioning
confidence: 93%
“…Breast cancer and its treatment have a huge effect on the psychological, social, emotional, and physical well-being of women with breast cancer [9]. The breast cancer treatment plan includes surgery, chemotherapy, radiation therapy, and hormonal therapy based on the stage of a cancer diagnosis for each patient [10]. In addition, breast cancer therapies have been linked with physical side effects such as a feeling of weakness and fatigue, appetite loss, hair loss, sore mouth, vomiting and nausea, and infertility [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…BC patients may experience long- and short-term complications and sequelae due to treatment or the disease itself, including alterations to quality of life, body composition, physical fitness and physical activity levels, heart rate, sleep and fatigue [ 16 20 ]. Lower levels of physical activity have also been reported to have a negative effect on quality of life and the risk of cancer recurrence [ 21 25 ].…”
Section: Introductionmentioning
confidence: 99%